0272 Thinning of Medial Frontal and Anterior Cingulate Cortices Explain Age-related Changes in REM and NREM Sleep. (27th April 2018) - Latreille, V; Gaubert, M; Dubé, J; Lina, J; Gagnon, J; Carrier, J
Abstract: Introduction: Accumulating evidence demonstrates a direct relationship between impaired neural integrity and disrupted sleep physiology in normal and pathological aging. However, previous work has focused almost exclusively on NREM sleep as a proxy of cortical integrity with aging. Whether this relationship holds true for REM sleep is unknown. This study investigated 1) the role of cortical thinning in modulating REM sleep EEG activity with aging; and 2) whether age-related EEG changes during both REM and NREM sleep can be accounted for by common brain substrates. Methods: Thirty young (16 men; 22.8 ± 2.8 years) and 29 healthy older adults (11 men; 59.5 ± 5.6 years) underwent polysomnographic recordings and anatomical 3T MRI scans. Relative EEG spectral power was computed on artifact-free epochs of REM and NREM sleep, and cortical grey matter integrity was assessed by cortical thickness (CT). Mediation analyses were performed to determine the role of CT in age-related REM and NREM sleep EEG changes. Results: Compared to younger adults, older adults showed more desynchronized EEG patterns during REM and NREM sleep, with lower delta power and higher power in theta and alpha bands. As expected, aging was associated with global cortical thinning. Mediation analyses revealed that reduced CT in the superior frontal gyrus, medial orbitofrontal, and anterior cingulate cortices explained the decrease in delta power during REM sleep with aging. Reduction in NREM delta power with age was also mediated by thinning of the superior frontal gyrus, medial orbitofrontal, and anterior cingulate cortices. Conjunction analysis revealed that reduced CT in the medial frontal and anterior cingulate cortices explained the age-related reduction in delta activity during both REM and NREM sleep. Conclusion: Our findings 1) support the potential role of the medial frontal and cingulate cortices, major hubs of the human brain, in synchronizing neuronal assemblies during sleep, and 2) suggest that with age, reduction in cortical integrity within this frontal network drives neuronal desynchrony during sleep, all of which may contribute to cognitive decline. Support (If Any): Canadian Institutes of Health Research.